Probing the Thermochromic Phase Transition in CuMoO4 by EXAFS Spectroscopy. Issue 11 (4th June 2018) - Jonane, Inga; Cintins, Arturs; Kalinko, Aleksandr; Chernikov, Roman; Kuzmin, Alexei
Abstract : Extended X‐ray absorption fine structure (EXAFS) spectroscopy at the Mo K‐edge is used to follow the thermochromic γ ‐to‐ α phase transition in copper molybdate (CuMoO4 ). The temperature dependence (10–300 K) of the radial distribution function (RDF) for the Mo–O atom pairs in the first coordination shell of molybdenum atoms is reconstructed by the regularization‐like method from the experimental EXAFS spectra. The analysis of the RDFs suggests that the transition occurs gradually within the two‐phase coexistence range of 225–275 K. The local environment of molybdenum atoms transforms upon the γ ‐to‐ α phase transition from strongly distorted octahedral to less distorted tetrahedral coordination. Abstract : The thermochromic γ ‐to‐ α phase transition in CuMoO4 is studied by Mo K‐edge extended X‐ray absorption fine structure spectroscopy in the temperature range of 10–300 K. The local atomic structure around molybdenum atoms changes upon the transition during heating from strongly distorted octahedral to less distorted tetrahedral coordination. The temperature dependence of the radial distribution function suggests that the transition occurs gradually within the two‐phase coexistence range of 225–275 K.